Alkali-responsive hydrophilic-hydrophobic conversion nano anti-erosion inhibition material as well as preparation method and application thereof

By using alkali-responsive nano-erosion-resistant materials in cement-based materials, the problems of low stability and utilization efficiency of the material in a strong alkaline environment are solved, and efficient media transmission suppression and corrosion resistance are achieved. , reducing application costs.

CN119118556APending Publication Date: 2024-12-13SOUTHEAST UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411112985.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing hydrophobic anti-dip media penetration materials have problems such as poor compatibility, poor stability in strong alkaline environments, low utilization efficiency and high application cost in cement-based materials, which makes it difficult to effectively inhibit the transmission and enrichment of corrosive media in practical applications. set.

Method used

Using alkali-responsive nano-erosion-resistant materials, the polymer slowly releases hydrophobic nanoparticles in an alkaline environment by coating alkali-responsive polymers on the surface of the hydrophobic nanomaterial, and realizes hydrophilicity by slowly releasing hydrophobic nanoparticles in an alkaline environment. The conversion to hydrophobic improves the dispersion and hydrophobic properties of the material.

Benefits of technology

It significantly improves the resistance to medium permeability and corrosion resistance of cement-based materials, reduces the water absorption rate and aggressive ion transmission of materials, improves the long-term corrosion resistance of materials, and reduces the application cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004992821510000091
    Figure BDA0004992821510000091
  • Figure BDA0004992821510000101
    Figure BDA0004992821510000101
  • Figure BDA0004992821510000102
    Figure BDA0004992821510000102
Patent Text Reader

Abstract

The invention discloses a nanometer anti-erosion material with alkali response hydrophilic-hydrophobic conversion as well as a preparation method and application of the nanometer anti-erosion material. The alkali-responsive hydrophilic-hydrophobic conversion nano anti-erosion material is prepared from a hydrophobized nano material and an alkali-responsive hydrophilic-hydrophobic conversion polymer material, the hydrophobic nano material is a nano particle with hydrophobicity; the alkali-responsive hydrophilic-hydrophobic conversion polymer is a functional polymer which can respond to change in an alkaline environment, slowly release hydrophobized nanoparticles and simultaneously generate hydrophilic-to-hydrophobic conversion. The alkali-responsive hydrophilic-hydrophobic conversion nano anti-erosion material can be applied to a cement-based material system, including but not limited to maritime work concrete, waterproof mortar, anticorrosive mortar, inorganic artificial stone and other cement-based materials, and the hydrophobicity of pores and pore interfaces of the cement-based materials is changed, so that the corrosion resistance of the cement-based materials is improved, and the corrosion resistance of the cement-based materials is improved. The medium permeation resistance and the corrosion resistance of the cement-based material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials and concrete admixture technology, and specifically relates to an alkali-responsive affinity-repellency conversion nano anti-corrosion inhibition material and a preparation method and application thereof. Background Art

[0002] Cement-based materials are the most widely used and used building materials in the world today. They are also the basic materials for industrial, civil construction, infrastructure, major projects, etc. With global warming and increasingly severe environmental changes, cement-based materials are facing increasingly severe material performance degradation and environmental considerations, and corrosion damage problems are becoming more and more prominent. Taking the most widely used concrete material as an example, it plays an important role in bridges, roads, tunnels, nuclear power and other fields. However, with the harsh service environment and extended service time, the frequent engineering accidents caused by the deterioration of structural concrete performance have become a global problem that has attracted widespread attention in today's engineering and academic circles.

[0003] Reducing the transmission of corrosive media in cement-based materials is the key to improving the corrosion resistance of cement-based materials themselves. Conventional technical means to reduce the transmission of media include: reducing the water-cement ratio (using high-performance water reducers to reduce water consumption) and using mineral admixtures (optimizing the interface transition zone and pore density). However, under harsh service environments, the above technical measures are still difficult to achieve the expected results. It is mainly reflected in: reducing the water-cement ratio and reducing water consumption will greatly affect workability and lead to construction difficulties; the use of mineral admixtures such as fly ash, mineral powder and silica fume may cause low early strength, aggravate carbonization depth and increase the risk of shrinkage cracking. In addition, from the type and severity of corrosion damage of cement-based materials, the transmission rate of various media in the dry-wet alternating zone is usually the fastest, and the corrosion process of cement-based materials is also the most serious. However, the improvement effect of the above technical measures in this regard is still not ideal. Existing studies have shown that the dry-wet alternating and splashing areas are the areas where cement materials such as concrete are most severely corroded. The main reason is that there is a capillary water absorption phenomenon similar to the "wick effect" in the above areas, and capillary water absorption will drive the rapid transmission and enrichment of corrosive ions. Therefore, reducing capillary water absorption becomes the key to inhibiting the transmission of corrosive media.

[0004] Internally mixed hydrophobic materials can reduce the interfacial energy of the internal pores of cement-based materials and their wettability with water, can effectively reduce the capillary adsorption of water inside pore structures such as capillaries, can significantly inhibit the rapid transmission and enrichment of water in the dry-wet alternating zone, and are also one of the measures that have been studied more in recent years and have shown excellent technical effects in improving the resistance of cement-based materials to medium penetration. (Construction and building materials 299 (2021) 124255) However, the existing internally mixed hydrophobic materials themselves have a more significant negative impact on the strength development of cement-based materials such as concrete, such as stearic acid emulsions generally reduce the strength of concrete by 15-30% (Construction and building materials 227 (2019) 11678), which buries hidden dangers for the protection of the mechanical properties of engineering structures. CN1106363C mentions that a hydrolyzable aqueous emulsion containing an organosilicon compound is added to fresh concrete before curing made of water, inorganic components and selective organic components for the preparation of uniform waterproof concrete, which can inhibit the transmission of corrosive media to a certain extent. However, when the concrete is fully saturated with water, this type of material has almost no effect on the diffusion of corrosive media, and sometimes increases the diffusion of corrosive ions in the concrete in the saturated state, thus failing to achieve the effect of inhibiting the transmission of the medium.

[0005] CN1233774C, CN102424542A etc. report a kind of nano silicon waterproofing agent, its composition is: sodium methyl silicate or sodium methyl siliconate or high boiling sodium siliconate, nanometer grade silicon dioxide, silicone acrylic emulsion or styrene acrylic emulsion or pure acrylic emulsion, monoethanolamine or diethanolamine or triethanolamine, deionized water.But waterproofing materials such as sodium methyl silicate can seriously affect the setting time of concrete, cause the actual amount used in application to be very limited, and be difficult to achieve the effect of efficient hydrophobicity under saturated water state simultaneously.In addition, adding nano material in cement-based material can also reduce the medium diffusion in concrete under saturated water state to a certain extent, but the poor stability of nano material itself and mixing in cement-based material are difficult to effectively and evenly disperse, cause its actual application effect to be still not ideal enough.

[0006] In addition, the existing internally mixed hydrophobic anti-corrosion materials have strong hydrophobicity, so when they are mixed into cement-based materials, the following common technical problems will occur:

[0007] (1) The compatibility of hydrophobic materials with cement-based materials is poor. Since hydrophobic materials are incompatible with water, the hydrophobic materials are easily unevenly dispersed during the mixing process of cement-based materials, and are prone to floating and precipitation after mixing, resulting in uneven overall anti-media penetration performance of cement-based materials;

[0008] (2) Cement-based materials are in a high-salt, highly alkaline environment. Existing hydrophobic materials have poor stability and are buried by hydration products before the hydration structure is formed. It is difficult to effectively exert the hydrophobic properties of the materials, resulting in low utilization efficiency.

[0009] (3) Due to the poor compatibility, high dosage, low utilization efficiency and other problems of existing hydrophobic anti-medium penetration materials, in order to achieve a better medium transmission inhibition effect in practical applications, a higher dosage is required, which also leads to high application costs of this technology and is difficult to promote widely. Summary of the invention

[0010] Purpose of the invention: In view of the problems of poor compatibility, poor stability in a strong alkaline environment, low utilization efficiency and high application cost of existing hydrophobic anti-media penetration materials, the purpose of the present invention is to provide a base-responsive affinity-dissipation conversion nano anti-corrosion inhibitory material with good compatibility, high stability in a strong alkaline environment and high utilization rate; another purpose of the present invention is to provide a method for preparing a base-responsive affinity-dissipation conversion nano anti-corrosion inhibitory material; another purpose of the present invention is to provide an application of a base-responsive affinity-dissipation conversion nano anti-corrosion inhibitory material.

[0011] Technical solution: The base-responsive affinity-phobic conversion nano-corrosion-resistant material of the present invention is composed of a hydrophobic nano-material and a base-responsive affinity-phobic conversion polymer material; wherein the base-responsive affinity-phobic conversion polymer material is coated on the outside of particles whose components are hydrophobic nano-materials; the hydrophobic nano-materials are nano-materials whose surfaces are treated with hydrophobic substances, or hydrophobic nano-particles prepared by a hydrophobic treatment process; the base-responsive affinity-phobic conversion polymer is a functional polymer that can respond to changes in an alkaline environment, slowly release hydrophobic nano-particles, and simultaneously undergo a hydrophilic to hydrophobic conversion transformation; the functional polymer is coated with the hydrophobic nano-particles to prepare the affinity-phobic conversion nano-corrosion-resistant material.

[0012] Furthermore, the hydrophobic nanomaterial is obtained by treating the nanoparticles with a hydrophobic substance; wherein the nanoparticles include but are not limited to nano-silicon dioxide, nano-titanium dioxide, nano-calcium carbonate, nano-calcium silicate and the like; the hydrophobic substance includes long-chain fatty acids or organic siloxanes and polysiloxanes, and representative fatty acids include organic carboxylic acids with a long chain or branched structure having a carbon chain length of 6 to 22; or alkyl siloxanes, polysiloxanes, etc. with a long chain or branched structure having an alkyl chain length of 4 to 20.

[0013] Furthermore, the hydrophobic nanomaterial also includes hydrophobic particles that have hydrophobic effects themselves, including but not limited to nano-scale zeolite powder, nanoparticles prepared from long-chain fatty acid salts with an alkyl chain length of 6 to 22, and the like.

[0014] Preferably, the particle size of the nano material is between 10 and 1000 nm, and preferably the particle size of the nano material is between 30 and 500 nm.

[0015] Preferably, the hydrophobic nanomaterial is selected from: hydrophobic fumed silica, hydrophobically modified nano silica particles, hydrophobically modified zeolite powder, modified nano calcium stearate and hydrophobically modified nano titanium dioxide; wherein the modifier used for the hydrophobic modification is isobutyl triethoxysiloxane, stearic acid or polydimethylsiloxane.

[0016] Furthermore, the base-responsive affinity-dissipation switching polymer material is a polyester or polyamide polymer. The polyester is a polymer obtained by condensation of a dibasic or tribasic carboxylic acid having 4 to 22 carbon atoms with ethylene glycol or polyethylene glycol; or a polyamide polymer obtained by condensation of a dibasic or tribasic carboxylic acid having an alkyl chain length of 2 to 20 with ethylenediamine or polyethylene polyamine.

[0017] Furthermore, the dicarboxylic acid may be a linear or branched dibasic or tribasic fatty acid, or a linear or branched dibasic or tribasic aromatic acid;

[0018] Furthermore, the molecular weight of the ethylene glycol or polyethylene glycol is 60 to 4000, and the further preferred molecular weight of the polyethylene glycol is 200 to 2000;

[0019] Furthermore, the molecular weight of the ethylenediamine or polyethylene polyamine is 100 to 4000, and the molecular weight of the polyethylene polyamine is preferably 200 to 2000;

[0020] The molecular weight of the base-responsive affinity-dissipation switching polymer is between 1,000 and 1,000,000, and the preferred molecular weight of the polymer is between 10,000 and 100,000.

[0021] On the other hand, the present invention provides a method for preparing the above-mentioned base-responsive affinity-phobic conversion nano-anticorrosion material, wherein a hydrophobic nano-material is coated in a base-responsive affinity-phobic conversion polymer material to obtain a nano-anticorrosion material whose outer shell layer is a base-responsive affinity-phobic conversion polymer and whose inner core is hydrophobic nanoparticles.

[0022] Specifically, the base-responsive affinity-repellency conversion nano anti-corrosion material is prepared by coating technology; the preparation technology includes but is not limited to mechanical mixing method, microemulsion coating method, etc.

[0023] Furthermore, the mechanical mixture method is to powderize the coating material, add it to the surface of the hydrophobized nanoparticles to be coated, and through mechanical mixing, make each component fully penetrate and diffuse to form a coating.

[0024] Furthermore, the microemulsion coating is to disperse the hydrophobic nanoparticles in an oil-in-water solution, and use the dispersion of an emulsifier to cover the coating material on the surface of the hydrophobic nanomaterial, thereby modifying the surface of the hydrophobic nanoparticles.

[0025] The hydrophilic-hydrophobic conversion nano anti-corrosion material of the present invention improves its dispersion uniformity in the concrete system by increasing its hydrophilicity, so as to avoid the negative impact of the premature hydrophobicity of the traditional hydrophobic material on the cement hydration; at the same time, the characteristics of the molecular structure of the coating material itself are utilized to realize the gradual enhancement of the hydrophobicity in the late stage of cement hydration, thereby achieving the hydrophilic-hydrophobic conversion.

[0026] On the other hand, the present invention provides an application of the above-mentioned alkali-responsive affinity-repellent conversion nano anti-corrosion material in the preparation of concrete, waterproof mortar, anti-corrosion mortar, cement-based waterproof coating, cement-based anti-corrosion coating or inorganic artificial stone. In the above-mentioned application, the alkali-responsive affinity-repellent conversion nano anti-corrosion material enhances the long-term corrosion resistance of cement-based materials by improving pore densification and hydrophobicity.

[0027] The hydrophobic-convertible nano-corrosion-resistant material of the present invention can be applied to concrete systems, and the strong alkalinity of the concrete system is utilized to realize the hydrophobic-convertible property, thereby significantly improving the hydrophobicity of the concrete pore interface, and further optimizing the compactness of the concrete pore structure, effectively preventing the transmission and accumulation of moisture and corrosive ions (chloride ions, sulfate ions, etc.) in concrete, and reducing the corrosion damage of corrosive media to concrete.

[0028] In addition, the nano anti-corrosion material with affinity-repellent conversion function of the present invention can also be applied to other cement-based material systems, including but not limited to waterproof mortar, anti-corrosion mortar, cement-based waterproof coating, cement-based anti-corrosion coating and inorganic artificial stone, etc. By adding the nano anti-corrosion material with affinity-repellent conversion function, the hydrophobicity of the cement-based material can be changed, thereby improving the long-term corrosion resistance of the cement-based material.

[0029] The nano anti-corrosion material with affinity-repellency conversion function of the present invention is more efficient than general anti-corrosion materials. When used in concrete or mortar systems, the general dosage is 0.1-5.0% relative to the mass fraction of the cementitious material. When used in other systems, it needs to be appropriately adjusted according to the application performance index requirements, and the dosage range can be appropriately increased.

[0030] The nano anti-corrosion material with affinity-repellency conversion function of the present invention can be diluted or compounded into an aqueous solution and added to concrete or mortar, and can replace water in equal amounts when added; it can also be made into a powder or solid and added to concrete, and can replace auxiliary cementitious materials in equal amounts.

[0031] The nano anti-corrosion material with affinity-repellency conversion function of the present invention is applied to structural concrete in harsh environments such as oceans and saline soils, effectively improving the medium penetration resistance and long-term corrosion resistance of cement-based materials, especially having a good corrosion inhibition effect on the corrosion damage of concrete or mortar in dry-wet alternating zones, and can also be applied to the durability improvement needs of cement-based materials in other service environments.

[0032] The nano anti-corrosion material with hydrophilic-hydrophobic conversion function of the present invention can also be used in waterproof or anti-corrosion mortar. Adding it into waterproof or anti-corrosion mortar can significantly improve the water resistance and corrosion resistance of the mortar, especially significantly improve the sulfate corrosion resistance of inorganic anti-corrosion mortar.

[0033] The nano anti-corrosion material with affinity-repellency conversion function of the present invention can also be applied to inorganic artificial stone prepared from cement-based materials, and can optimize and improve the porosity of inorganic artificial stone, reduce the water absorption rate of inorganic artificial stone, and enhance the water resistance, stain resistance and corrosion resistance of inorganic artificial stone.

[0034] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) Since the alkali-responsive hydrophilic-lipophilic conversion functional polymer itself has adjustable hydrophilic-lipophilic properties, the initial hydrophobicity of the hydrophobic nanomaterial can be improved by enhancing the hydrophilicity during the material preparation process, thereby avoiding the influence of directly adding the hydrophobic nanomaterial on cement hydration and concrete performance. At the same time, the regulation of hydrophilicity can further improve the dispersion performance of the hydrophobic anti-corrosion material in concrete, thereby improving the utilization efficiency of the anti-corrosion material.

[0035] (2) The functional polymer of the alkali-responsive affinity-repellency conversion is an ester bond or an amide bond, which can be slowly hydrolyzed in the alkaline environment of concrete. After hydrolysis, the ester bond or the amide bond breaks, and the surface coating material slowly dissolves, releasing the hydrophobic nanomaterial. The further released carboxyl groups and hydrophobic nanoparticles will participate in the cement hydration reaction to generate hydrophobic compounds, and change the wettability and surface energy of the hydration product interface, thereby producing an efficient hydrophobic effect, in which the hydrophobicity is not only provided by the hydrophobic nanoparticles, but also includes the part of the affinity-repellency conversion functional polymer that participates in the cement hydration reaction after hydrolysis, so the hydrophobic resistance to medium penetration is further improved;

[0036] (3) The polymer molecules with affinity-repellency conversion function of the present invention have the function of adjustable sustained release time. By adjusting the sustained release time, the function of not releasing in the early stage of cement hydration and releasing in the later stage can be achieved. The influence of premature hydrophobization on the microstructure formation of cement hydration products can be effectively avoided, thereby optimizing the pore structure of concrete and long-term anti-media penetration performance. DETAILED DESCRIPTION

[0037] The affinity-repellent conversion nano anti-corrosion material of the present invention is prepared by three steps, wherein the first step is the preparation of hydrophobic nanoparticles, the second step is the preparation of affinity-repellent conversion functional polymers, and the third step is to coat the hydrophobic nanomaterials with affinity-repellent conversion functional polymers, and finally the affinity-repellent conversion nano anti-corrosion material is prepared.

[0038] In the first step, the hydrophobic nanoparticles can also be obtained by purchasing commercially available hydrophobic nanomaterials, wherein the commercially available hydrophobic nanoparticles include, but are not limited to, hydrophobic nano-silicon dioxide, hydrophobic silica polymers, hydrophobic zeolite powder, hydrophobic nano-calcium carbonate powder, and other nano-sized hydrophobic agent products.

[0039] In the second step, the functional polymer for affinity-phobic conversion is prepared by the preparation method disclosed in the present invention, and the raw materials used are all chemical raw materials.

[0040] In the third step, the nanomaterial coating preparation process is the coating technology disclosed in the present invention, and the material is coated by powder material blending or microemulsion coating, and finally the nano anti-corrosion material with affinity-repellency conversion function described in the present invention is prepared.

[0041] The affinity-repellency conversion nano anti-corrosion material of the present invention is mainly used in concrete and cement-based material systems to improve and enhance the medium penetration resistance and corrosion resistance of concrete or cement-based materials.

[0042] In order to better illustrate the beneficial effects of the present invention, the preparation and application examples of several materials are listed below. The "parts" in the following examples refer to parts by weight. The following examples are merely illustrative and do not limit the scope of application of the present invention. According to the disclosure herein, those skilled in the art can change the reagents, catalysts and reaction process conditions within the scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0043] Material Preparation Example

[0044] Embodiment 1:

[0045] This example illustrates the preparation process of a nano anti-corrosion material using commercially available hydrophobic fumed silica (product model SHP 50) via a polymer having an affinity-phobic conversion function.

[0046] Step 1: Take 20 parts of succinic acid, 30 parts of polyethylene glycol with a molecular weight of 1000 and 0.1 parts of concentrated sulfuric acid, add them into a reaction kettle, heat to 140°C, react for 8 hours, and prepare a polymer with affinity-dissipation conversion function for use.

[0047] Step 2: Add 50 parts of commercially available SHP 50 fumed silica and 5 parts of the polymer with affinity-repellent conversion function prepared in step 1 into a mechanical mixer, and then add 45 parts of silica fume powder, and coat the hydrophobic nanoparticles with the affinity-repellent conversion functional polymer through sufficient mechanical mixing to prepare the nano anti-corrosion material S1 with affinity-repellent conversion function.

[0048] Embodiment 2:

[0049] This example lists the preparation process of a nano anti-corrosion material prepared by coating a homemade hydrophobic nano material with a polymer having a pro-phobic conversion function. The raw materials used in the preparation of the hydrophobic nano material are nano calcium carbonate and isobutyl triethoxysiloxane; the raw materials used in the pro-phobic conversion polymer are lauric acid and polyethylene glycol with a molecular weight of 800; and the surface coating of the hydrophobic nano material is prepared by physical blending.

[0050] Step 1: Add 30 parts of nano calcium carbonate with a particle size of 50 nm to 60 parts of ethanol solution, stir well, continue to add 5 parts of isobutyl triethoxy silane impregnating agent, stir well, continue to add 0.1 parts of ammonia water, control the temperature at 40 ° C, react for 10 hours, recover the ethanol solution by rotary distillation, and finally obtain hydrophobically modified nano silica particles.

[0051] Step 2: Take 10 parts of dodecanoic acid, 40 parts of polyethylene glycol with a molecular weight of 800 and 0.1 parts of p-toluenesulfonic acid, add them into a reaction kettle, heat to 160° C., react for 6 hours, and prepare a polymer with affinity-dissipation conversion function for use.

[0052] Step three: Take 60 parts of the hydrophobic nanoparticles prepared in step one and 8 parts of the polymer with affinity-phobic conversion function prepared in step two, add them into a mechanical mixer, and then add 32 parts of fly ash powder. Through sufficient mechanical mixing, the functional polymer with affinity-phobic conversion is coated on the hydrophobic nanoparticles to prepare nano anti-corrosion material S2 with affinity-phobic conversion function.

[0053] Embodiment 3:

[0054] This embodiment lists the preparation process of a nano anti-corrosion material prepared by coating a homemade hydrophobic nano material with a polymer having an affinity-phobic conversion function. The nano material used is zeolite powder, and the hydrophobic substance is stearic acid; the polymer having an affinity-phobic conversion function is a polyamide organic matter, and the raw materials used for the preparation are trimesic acid and tetraethylenepentamine; the surface coating of the hydrophobic nano material is carried out by a microemulsion preparation method.

[0055] Step 1: Add 40 parts of nano-zeolite powder to 50 parts of tetrachloromethane solution, stir well, continue to add 2 parts of stearic acid, stir well, raise the temperature to 80°C, react for 8 hours, recover tetrachloromethane by rotary distillation, and finally obtain hydrophobically modified zeolite powder.

[0056] Step 2: Take 20 parts of trimesic acid, 50 parts of tetraethylenepentamine and 0.2 parts of triethylamine, add them into a reaction kettle, heat to 170°C, react for 12 hours, and prepare a polymer with affinity-dissipation conversion function for use.

[0057] Step 3: Take 0.5 parts of emulsifier and 50 parts of water, stir evenly, then add 40 parts of hydrophobic nanoparticles prepared in step 1, stir at high speed for 30 minutes, slowly add 5 parts of the polymer prepared in step 2 and 5 parts of dimethyl sulfoxide as a mixed solution, continue to stir at high speed for 2 hours after the addition is complete, and prepare the nano anti-corrosion material S3 with affinity-disappointment conversion function.

[0058] Embodiment 4:

[0059] This example illustrates the preparation process of a nano anti-corrosion material using commercially available modified nano calcium stearate G-150 through a polymer with affinity-dissipation conversion function.

[0060] Step 1: Take 30 parts of phthalic acid, 50 parts of polyethylene glycol with a molecular weight of 4000 and 0.2 parts of concentrated sulfuric acid, add them into a reaction kettle, heat to 170°C, react for 6 hours, and prepare a polymer with affinity-dissipation conversion function for use.

[0061] Step 2: Add 40 parts of commercially available nano-calcium stearate and 6 parts of the polymer with affinity-dissipation conversion function prepared in step 1 into a mechanical mixer, and then add 44 parts of fly ash. Through sufficient mechanical mixing, the functional polymer with affinity-dissipation conversion is coated on the nano-calcium stearate to prepare nano-anti-corrosion material S4 with affinity-dissipation conversion function.

[0062] Embodiment 5:

[0063] This example lists the preparation process of a self-made hydrophobic nanomaterial coated with a polymer having an affinity-repellent conversion function to prepare a nano-corrosion-resistant material. The raw materials used in the preparation of the hydrophobic nanomaterial are nano-titanium dioxide and polydimethylsiloxane (PDMS); the raw materials used in the affinity-repellent conversion polymer are octadecanedioic acid and polyethylene glycol with a molecular weight of 3000; the surface coating of the hydrophobic nanomaterial is prepared by physical blending.

[0064] Step 1: Add 25 parts of nano-titanium dioxide with a particle size of 50 nm to 50 parts of ethanol solution, stir well, add 6 parts of polydimethylsiloxane (PDMS), stir well, add 0.3 parts of ammonia water, control the temperature at 60°C, react for 24 hours, recover the ethanol solution by rotary distillation, and finally obtain hydrophobically modified nano-silica particles.

[0065] Step 2: Take 10 parts of octadecane dioic acid, 40 parts of polyethylene glycol with a molecular weight of 3000 and 0.2 parts of concentrated sulfuric acid, add them into a reaction kettle, heat to 180°C, react for 10 hours, and prepare a polymer with affinity-dissipation conversion function for use.

[0066] Step three: Take 55 parts of the hydrophobic nanoparticles prepared in step one and 10 parts of the polymer with affinity-phobic conversion function prepared in step two, add them into a mechanical mixer, and then add 35 parts of mineral powder. Through sufficient mechanical mixing, the functional polymer with affinity-phobic conversion is coated with the hydrophobic nanoparticles to prepare nano anti-corrosion material S5 with affinity-phobic conversion function.

[0067] Embodiment 6:

[0068] This embodiment lists the preparation process of a nano anti-corrosion material prepared by coating a homemade hydrophobic nano material with a polymer having an affinity-repellent conversion function. The nano material used is nano calcium silicate, and the hydrophobic substance is octyltriethoxysilane; the polymer having an affinity-repellent conversion function is a polyamide organic matter, and the raw materials used for the preparation are eicosyl diacid and polyethylene polyamine; the surface coating of the hydrophobic nano material is carried out by a microemulsion preparation method.

[0069] Step 1: Add 40 parts of nano calcium silicate to 40 parts of dichloromethane solution, stir well, continue to add 10 parts of octyltriethoxysilane, stir well, raise the temperature to 60°C, react for 7 hours, recover dichloromethane by rotary distillation, and finally obtain hydrophobic modified nano calcium silicate.

[0070] Step 2: Take 30 parts of eicosyl diacid, 10 parts of polyethylene polyamine and 0.1 parts of triethylamine, add them into a reaction kettle, heat to 140°C, react for 3 hours, and prepare a polymer with affinity-dissipation conversion function for use.

[0071] Step three: Take 1 part of emulsifier and 55 parts of water, stir evenly, then add 34 parts of hydrophobic nanoparticles prepared in step one, stir at high speed for 30 minutes, slowly add a mixed solution composed of 7 parts of polyamide polymer prepared in step two and 3 parts of dimethyl sulfoxide, and continue to stir at high speed for 3 hours after the addition is complete to prepare nano anti-corrosion material S6 with affinity-phobic conversion function.

[0072] Application Examples

[0073] This section lists the application examples of the materials. The application examples listed are only representative of the application of the materials of the present invention in different cement-based materials. Other cement-based materials similar to the application examples can also be used. Application Example 1: Application in Concrete System

[0074] The application of alkali-responsive affinity-repellency conversion nano-anti-corrosion materials in concrete systems can effectively improve the concrete's resistance to medium penetration, and has a good inhibitory effect on chloride ion penetration, sulfate corrosion, and capillary adsorption and enrichment in dry-wet alternating environments.

[0075] This application example lists the application of the alkali-responsive affinity-repellency conversion nano anti-corrosion material of the present invention in common marine engineering concrete to improve the durability of concrete. The selected marine engineering concrete ratio is the commonly used marine engineering concrete ratio, and the specific ratio is shown in Table 1. The above-mentioned nano anti-corrosion material is added during the preparation of concrete. The application example also selects the commonly used hydrophobic nano material on the market that has not been modified by affinity-repellency conversion functional materials for comparison. The selected material is the organosilicon hydrophobic agent SHP 60 Dow Corning hydrophobic agent with good performance on the market, code-named SHP 60.

[0076] Table 1 Concrete mix ratio kg / m 3

[0077]

[0078] The effects of different samples on the workability, mechanical properties, hydrophobicity and chloride ion diffusion resistance of concrete were compared and studied. The water absorption rate was tested according to BS1882, and the chloride ion diffusion coefficient was tested according to the electromigration chloride ion diffusion coefficient RCM method in GB50082 "Test method for medium- and long-term durability of ordinary concrete". The test results are shown in Table 3.

[0079] Table 2 Effect of different samples on concrete performance

[0080]

[0081] The test results show that the addition of alkali-responsive nano-corrosion-resistant materials with affinity-repellent conversion has little effect on the working performance and mechanical properties of concrete, and can reduce the water absorption rate of concrete at the same time. The reduction pattern is that the reduction in water absorption rate in the early stage is relatively small, and the reduction in water absorption rate in the later stage is significant. The reduction in water absorption rate in the later stage is compared with similar silicone hydrophobic agents, and the hydrophobic performance is stronger, which reflects the affinity-repellent conversion effect of the present invention. In addition, the results of the electromigration diffusion coefficient also show that the chloride ion diffusion coefficient of concrete with the addition of alkali-responsive nano-corrosion-resistant materials with affinity-repellent conversion is significantly reduced, indicating that the compactness of the concrete is effectively improved, and the enhancement of the later anti-medium penetration performance is truly achieved.

[0082] Application Example 2: Application in waterproof mortar system

[0083] The raw materials used for waterproof mortar are the same as those used for concrete. The specific formula of the waterproof mortar is shown in Table 3.

[0084] Table 3 Waterproof mortar mix ratio kg / m 3

[0085]

[0086]

[0087] Table 4 Waterproof mortar performance

[0088]

[0089] The test results show that the addition of alkali-responsive nano-anti-corrosion material mortar with affinity-repellent conversion has little effect on the air content, consistency and water retention rate, and does not reduce the mechanical properties. At the same time, it can significantly reduce the water penetration depth of the mortar, and the water penetration is smaller than that of similar silicone hydrophobic agents, indicating that the affinity-repellent conversion anti-corrosion material of the present invention has better effect.

Claims

1. A base-responsive nano-corrosion-resistant material with affinity-dissipation conversion, characterized in that: The invention is composed of a hydrophobic nanomaterial and a polymer material capable of switching between hydrophilicity and hydrophobicity in response to alkali; wherein the polymer material capable of switching between hydrophilicity and hydrophobicity in response to alkali is coated on the outside of particles whose components are hydrophobic nanomaterials; the hydrophobic nanomaterials are nanomaterials whose surfaces are treated with hydrophobic substances, or hydrophobic nanoparticles prepared by a hydrophobic treatment process; the polymer material capable of switching between hydrophilicity and hydrophobicity in response to alkali is a functional polymer capable of responding to changes in an alkaline environment, slowly releasing hydrophobic nanoparticles, and simultaneously undergoing a transition from hydrophilicity to hydrophobicity.

2. The base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 1, characterized in that: The hydrophobic nanomaterial is obtained by treating nanoparticles with a hydrophobic substance; wherein the nanoparticles are selected from: nano-silicon dioxide nanoparticles, nano-titanium dioxide nanoparticles, nano-calcium carbonate nanoparticles, nano-calcium silicate nanoparticles; and the hydrophobic substance is a long-chain fatty acid, an organic siloxane or a polysiloxane.

3. The base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 2, characterized in that: The hydrophobic substance is selected from: organic carboxylic acids with a carbon chain length of 6 to 22, long chain or branched structures, alkyl siloxanes with an alkyl chain length of 4 to 20, and long chain or branched structures of polysiloxanes with an alkyl chain length of 4 to 20.

4. The base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 1, characterized in that: The hydrophobic nanomaterial is a hydrophobic particle having a hydrophobic effect, selected from: nano-grade zeolite powder, nanoparticles prepared from long-chain fatty acid salts with an alkyl chain length of 6 to 22, and the particle size of the hydrophobic nanomaterial is 10 to 1000 nm.

5. The base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 1, characterized in that: The base-responsive affinity-dissipation conversion polymer material is a polyester or polyamide polymer; the polyester is a polymer obtained by condensation of a dibasic or tribasic carboxylic acid having 4 to 22 carbon atoms with ethylene glycol or polyethylene glycol; or a polyamide polymer obtained by condensation of a dibasic or tribasic carboxylic acid having an alkyl chain length of 2 to 20 with ethylenediamine or polyethylene polyamine.

6. The base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 5, characterized in that: The dicarboxylic acid is selected from: linear or branched dibasic or tribasic fatty acids, linear or branched dibasic or tribasic aromatic acids.

7. A method for preparing a base-responsive affinity-repellency conversion nano anti-corrosion material according to any one of claims 1 to 6, characterized in that: The hydrophobic nanomaterial is coated in the base-responsive affinity-phobic switching polymer material to obtain a nano anti-corrosion material with an outer shell layer of the base-responsive affinity-phobic switching polymer and an inner core of hydrophobic nanoparticles.

8. The method for preparing the base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 7, characterized in that: The hydrophobicized nanomaterials are encapsulated in the base-responsive hydrophobic-switching polymer material by mechanical mixing or microemulsion encapsulation.

9. The method for preparing the base-responsive affinity-dissipation switching nano anti-corrosion material according to claim 8, characterized in that: The mechanical mixture method is to treat the coating material into powder, add it to the surface of the hydrophobized nanoparticles to be coated, and make each component fully penetrate and diffuse through mechanical mixing to form a coating; the microemulsion coating is to disperse the hydrophobized nanoparticles in an oil-in-water solution, and use the dispersion of an emulsifier to cover the coating material on the surface of the hydrophobized nanoparticles, thereby modifying the surface of the hydrophobized nanoparticles.

10. Use of the base-responsive affinity-repellency conversion nano anti-corrosion material according to any one of claims 1 to 6 in the preparation of concrete, waterproof mortar, anti-corrosion mortar, cement-based waterproof coating, cement-based anti-corrosion coating or inorganic artificial stone.

Citation Information

Cited By

  • Concrete hydrophilic-to-hydrophobic material based on one-way regulation and control of pH value and preparation method of concrete hydrophilic-to-hydrophobic material

    CN119461947A

  • Concrete composite coating suitable for power transmission and transformation station structure in salinized soil area and preparation method of concrete composite coating

    CN119775810A